Predictive control of residential HVAC and its impact on the grid. Part I: simulation framework and models. Issue 3 (4th May 2017) - Corbin, C.D.; Henze, G.P.
Abstract : This paper presents and discusses the methodology used in a numerical investigation of the aggregated effect of model predictive control (MPC) strategies implemented in hundreds of residential buildings on demand reduction in the electricity distribution feeder. This approach includes reduced order models for the homes and heating, ventilating and air conditioning systems, a model for typical group of buildings served by a distribution feeder, and a simple model for the description of real and reactive power flows. The methodology is demonstrated with a simple MPC example. This paper is intended to serve as the basis of a study, presented in the companion paper, on the effect of using residential predictive control strategies to complement the integration of renewable energy technologies in the grid.